Temporal Dynamics of Power Distribution in Mobile Urban Co-Policies: A Southern Analytical Framework - Laura Sobral; Predrag Milić; Burcu Ateş (Urban Planning)
This study proposes an analytical framework for scrutinising the temporal dynamics of power distribution within the mobility of urban co-policies, particularly those that aim to enhance socio-spatial justice. The role of time in shaping power dynamics in the new contexts covered by urban co-policies is central to this analysis. The framework is constructed through a comprehensive literature review and empirical fieldwork on the Lisbon mobile co-policy, called Bairros de Intervenção Prioritária/Zonas de Intervenção Prioritárias, which is supplemented by analysis of participatory and contextual policies across cities within the Com.Unity.Lab Transfer Network. Drawing on theories of policy mobility in the context of Southern epistemologies, the framework underscores the significance of temporal dynamics in the formation of policy outcomes, which highlights the necessity of the continuous assessment of policy intermediary results over time. The proposed framework identifies a gap in the analysis of the mobility of co-policies that integrate spatial co-production and co-governance at the neighbourhood scale. Methodologically based on the Southern ethics of inquiry in which time serves as a critical lens through which travelling co-policies are understood, the study offers insights into the need for continuous adaptation with the overarching goal of assessing the extent to which urban co-policies can foster social justice towards fairer cities.